Model Proses Kewirausahaan PD Hikmat Kabupaten Purwakarta - Mulyani, Dewi; Wulandari, Tresna (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This study uses qualitative and descriptive methods and aims to determine the entrepreneurial process of PD Hikmat owner who has 37 years of business experience, starting from the beginning of establishment, development, to the stage of business growth, along with the factors that influence it, as well as the obstacles and challenges faced by owner during entrepreneurship. The owner of PD Hikmat started his business because he wanted to improve the family's income and there were business opportunities in Purwakarta where there were not many competitors. PD Hikmat began to develop when observing new opportunities to collaborate with catering entrepreneurs. PD Hikmat experienced business growth when the owner began to imitate the modernization of similar entrepreneurs. PD Hikmat found business challenges and obstacles during the rainy season and rising raw material prices. PD Hikmat has competitive advantages, personal qualifications of the owner, distinctive product taste, adequate product inventory, employee loyalty, good relations with stakeholders. The current challenges and opportunities for PD Hikmat are marketing and packaging products creatively, and meet consumer preferences for healthier and more natural processed food products.